Kaidah Fiqhiyyah Yang Berkaitan Tentang Hadhanah - Dahanum, Wani; Muhammad Amar Adly; Heri Firmansyah (Albayan Journal of Islam and Muslim Societies, 2025)
This paper aims to examine kaidah fiqhiyyah (the principles) regarding hadhanah (child custody). The discussion covers the definition, meaning, legal basis, and application of these principles in Islamic family law concerning hadhanah issues. This article also explores certain conditions that constitute exceptions to the main principles under discussion. The research employs a normative juridical method with a literature study approach. It analyzes primary legal sources such as the Qur’an and Hadith, classical Islamic legal texts, and statutory regulations. Secondary legal sources are also utilized, including scholarly journals, legal literature, and electronic media. The findings of this study indicate that based on the examined fiqhiyyah principles, it can be concluded that from the perspective of Islamic law, child custody is prioritized to the mother and her side of the family. This is because the mother plays a dominant role in providing affection and care for the child.